Effect of Static Contraction on The Rate of Healing of Perineal Wounds in Postpartum Mothers with Perineal Tears - Nurhayati, Rina; Rahmawati, Nurul Aini; Yulianti, Atika (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Static contraction is an isometric muscle contraction exercise without any modification of muscle length and without any activity in the joints which is beneficial to increase muscle strength. Static contraction with kegel exercise is beneficial in accelerating the wound healing process of perineal tears. Based on WHO data, almost 90% of normal labor methods experience tears either with or without episiotomy. Methods: This study used a Quasi-experimental research method. The population obtained was 24 people. A total of 20 people were used as samples in this study which were divided into treatment groups and control groups. Static contraction exercises were given to the treatment group and stretching was given to the control group. Measurement of wound healing rate was measured using REEDA Scale. Results: The results of the Wilcoxon range test in the treatment group had a p value = 0.005 which indicated a significant effect and in the control group had a p value = 0.003 which indicated a significant effect. Then the mann-whitney test was carried out to determine the difference in influence between the treatment group and the control group of static contraction variables on the healing rate of perineal wounds with the results of the p value = 0.045 which means that there is a significant difference in influence between the treatment group and the control group. Conclusion: there is an effect of static contraction on the rate of healing of perineal wounds in spontaneous birth postpartum mothers with perineal tears. Pendahuluan: Static contraction adalah latihan kontraksi otot isometrik tanpa adanya perubahan panjang otot dan tanpa adanya gerakan pada sendi yang bermanfaat meningkatkan kekuatan otot. Statik kontraksi dengan kegel exercise bermanfaat dalam mempercepat proses penyembuhan luka pada robekan perineum. Berdasarkan data WHO nyaris 90% metode persalinan normal mengalami tears baik dengan atau tanpa episiotomi Metode: Penelitian ini menggunakan desain penelitian Quasi eksperimental. Populasi yang didapat sebanyak 24 orang dengan jumlah sampel yang digunakan sebanyak 20 responden yang dibagi menjadi kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen diberikan statik kontrak dua kali satu hari dan kelompok kontrol diberikan stretching. Pengukuran tingkat kesembuhan luka diukur menggunakan REEDA Scale. Hasil: Hasil uji wilcoxon range test pada kelompok eksperimen memiliki nilai p= 0,005 yang menunjukkan adanya pengaruh yang signifikan dan pada kelompok kontrol memiliki nilai p= 0,003 yang menunjukkan adanya pengaruh yang signifikan. Kemudian dilakukan uji mann-whitney untuk mengetahui perbedaan pengaruh antara kelompok eksperimen dan kelompok kontrol variabel statik kontraksi terhadap tingkat kesembuhan wound perineal dengan hasil nilai p= 0,045 yang menunjukkan adanya perbedaan pengaruh yang signifikan antara kelompok eksperimen dan kelompok kontrol. Simpulan: terdapat pengaruh statik kontraksi terhadap tingkat kesembuhan wound perineal pada ibu post partum kelahiran spontan dengan robekan perineum.